2021
DOI: 10.1590/1678-7757-2020-0865
|View full text |Cite
|
Sign up to set email alerts
|

A novel acrylic resin palatal device contaminated with Candida albicans biofilm for denture stomatitis induction in Wistar rats

Abstract: A novel acrylic resin palatal device contaminated with Candida albicans biofilm for denture stomatitis induction in Wistar rats Denture stomatitis is the most frequent oral lesion in removable prosthesis wearers, with high recurrence rates and a complex treatment. Objective: This study describes a protocol to obtain and to contaminate a palatal device with Candida albicans biofilm that could be used for an animal model of denture stomatitis. Methodology: Acrylic resin devices (N=41) were obtained from impressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Ill fitted devices can either be lost through the course of the experiment or make the palatal tissue more susceptible to fungal infestation, considering it would probably cause more local trauma. 31 Moraes et al 4 modified the design developed by Hotta et al 33 by proposing the use of a colorless autopolymerizing acrylic resin to fabricate the palatal devices, in order to allow visibility during adaptation and fixation (Figure 6). The authors stated that visibility during experiments is essential, since any defect on the surface of the devices might compromise their adaptation and stabilization in the oral cavity.…”
Section: Palatal Acrylic Devices For Ratsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ill fitted devices can either be lost through the course of the experiment or make the palatal tissue more susceptible to fungal infestation, considering it would probably cause more local trauma. 31 Moraes et al 4 modified the design developed by Hotta et al 33 by proposing the use of a colorless autopolymerizing acrylic resin to fabricate the palatal devices, in order to allow visibility during adaptation and fixation (Figure 6). The authors stated that visibility during experiments is essential, since any defect on the surface of the devices might compromise their adaptation and stabilization in the oral cavity.…”
Section: Palatal Acrylic Devices For Ratsmentioning
confidence: 99%
“…These authors also tested different fixation methods for the devices (two autopolymerizing acrylic resins or a self-adhesive resin cement) and concluded that the latter was the best stabilization material, especially because it does not promote any thermal reaction that may compromise the palatal mucosa of the animals. 4 Lee et al 36 developed a more complex device consisting of a fixed part that is anchored to the posterior palate by orthodontic wires and acrylic resin and a removable part fitted to the anterior palate that is retained by magnets embedded in the fixed part (Figure 7). One of the main advantages of this type of device is the ability to monitor fungal colonization longitudinally.…”
Section: Palatal Acrylic Devices For Ratsmentioning
confidence: 99%
See 3 more Smart Citations